Two new species of the genus Peltonotellus Puton (Hemiptera: Fulgoromorpha: Caliscelidae) from northwestern China with a world checklist - Meng, Rui; Gnezdilov, Vladimir M.; Wang, Yinglun (Zootaxa, 2015)
A checklist of Peltonotellus species is provided. Two new species, P. brevis sp. nov. from Ningxia Hui Autonomous Region and P. niger sp. nov. from Gansu Province are described and illustrated. Chinese species of the genus Peltonotellus as well as sexual dimorphism are briefly discussed.